A revision of the South American genus Metecia Snellen (Lepidoptera, Noctuidae, Noctuinae) - Navarro, Fernando R.; Barrionuevo, M. Jose; Blas, German San (Zootaxa, 2015)
The genus Metecia Snellen (Noctuidae. Noctuinae) from Southern Argentina and Chile is redescribed and three species are recognized: M. cornifrons Snellen, M. lacustris (Köhler) n. comb., and M. hypothetica (Köhler) n. comb. In addition, Euxoa pampeana Köhler is synonymized with Metecia cornifrons. Adults and male and female genitalia are described and illustrated for the first time, and a key to the species is provided.